NILAI-NILAI TASAWUF SEBAGAI BASIS TEO-PSIKOLOGIS DALAM PATOLOGI SIBER: TINJAUAN LITERATUR NARATIF - Yunandia; Nabila Marwah Safira; Rismaya Wulandari; Afila Fitroh Rohmawati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Studies on Sufism values as a theo-psychological basis for strengthening self-control tend to be examined partially. This study is to investigate the incorporation and impact of Sufism values for self-control in the digital age, in the context of cyber pathology. a qualitative literature review method with comparative analysis of various studies on digital psychology, cyber pathology, and Sufism values. Data were collected from Google Scholar, SINTA, Publish or Perish, and Mendeley Desktop, with publication criteria ranging from 2023 to 2026. The research procedures included identification, relevance screening, data reduction, tabulation, data extraction, and comparative analysis. The findings indicate that external approaches, such as legal regulations and digital literacy, remain insufficient in overcoming digital behavioral problems. The internalization of Sufism values addresses the individual’s inner dimensions and provides a preventive approach through integration with psychological concepts, namely tazkiyatun nafs, muraqabah, muhasabah, and mujahadah. These values are actualized through dhikr, zuhud, qana’ah, tawakal, tabayyun, and sabr to develop awareness, regulate emotions, and reduce digital dependence and the need for digital validation. Their implementation includes character education, digital literacy development, family parenting, as well as moral and mental health development programs grounded in theo-psychology. Sufism as a relevant means for shaping digital behavior.